Sociality as the Human Condition Anthropology in Economic, Philosophical and Theological Perspective. - Klein, Rebekka A. (Philosophical Studies in Science and Religion, 2011)
In addition to being contemplated in the classical disciplines of anthropology, human sociality has been subjected to scientific examination in the natural and social sciences. This book offers a substantial discussion of empirical research programs within current economics (experimental and neuroeconomics), with special regard to the themes of reciprocity and altruism. These themes are discussed from a philosophical perspective informed by phenomenology and hermeneutics, and linked to theories of conflict, recognition and alterity in social philosophy, which are used to show the limitations of the purely science-based naturalistic approaches in economics. Finally, the book introduces the concept of the neighbor in Christian theology and shows how this figure brings a new perspective to the examination of human sociality.